Factors Influencing Customer Decisions in Mortgage Financing Ib: A Perspective Analysis of Sharia Economic Law - Sholikul Hadi; Ija Suntana; Deni Kamaludin Yusup; Eri Novari (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Islamic mortgage financing (KPR iB) is one of the flagship products of Islamic banking in Indonesia, designed to facilitate home ownership in accordance with Sharia principles. However, customer participation in KPR iB remains suboptimal compared to conventional mortgage products. This study aims to examine the factors influencing customer decisions in choosing KPR iB, particularly from the perspective of Islamic Economic Law. The study specifically analyzes: (1) the influence of Sharia compliance, product innovation diffusion, promotion, and product quality on customer decisions to choose KPR iB in Bogor; and (2) the mediating role of customer decisions in the relationship between those variables and the increase of Islamic bank market share. This research employs a Mixed Methods approach, with an Explanatory Sequential Design combining quantitative and qualitative analyses. The theoretical framework includes Rational Choice Theory (Gary Becker) as the Grand Theory, Islamic Consumer Behavior Theory (Umer Chapra) as the Middle Theory, and Sharia Compliance Theory (Monzer Kahf) as the Application Theory. Data were collected through questionnaires, observations, interviews, and document analysis. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The findings indicate that: (1) Sharia compliance does not significantly influence customer decisions; (2) product innovation, promotion, and product quality have a significant positive effect on customer decisions; and (3) customer decision does not mediate the relationship between Sharia compliance and market share, but effectively mediates the impact of product innovation, promotion, and product quality on increasing Islamic bank market share.